THERMAL PERFORMANCE ASSESSMENT IN A CIRCULAR TUBE FITTED WITH VARIOUS SIZES OF MODIFIED V-BAFFLE: A NUMERICAL INVESTIGATION - Withada Jedsadaratanachai; Amnart Boonloi (My University, 2021)
A premiere free-access and peer-reviewed frontier journal site, serving the needs of the thermal-fluids community. See the latest research or submit an article. Quickly share your research with the global thermal-fluids community, for increased citations and impact at no cost.
Keywords: Baffle; Thermal fluids; Frontier; Spacecraft and Cryogenic Technologies